Therapeutic alliance during trauma focused treatment in adolescent and young adult patients with PTSD - Anne Grass; Rita Rosner; Angelina Ciner; Babette Renneberg; Regina Steil (BMC Psychiatry)
Abstract Background Greater therapeutic alliance has been associated with an improved treatment outcome in various clinical populations. However, there is a lack of evidence for this association in posttraumatic stress disorder (PTSD) in young patients. We therefore investigated the development of the therapeutic alliance during Developmentally adapted cognitive processing therapy (D-CPT) in adolescents and young adults with PTSD following abuse to answer the question whether there was a connection between the therapeutic alliance and symptom reduction. Methods Weekly assessments of therapeutic alliance, rated by patients and their therapists, as well as PTSD symptom severity from a randomized controlled trial (RCT) of D-CPT were analyzed with multilevel modelling. The sample consisted of n = 39 patients aged 14–21 with a history of sexual and/or physical abuse. Results Therapeutic alliance increased during D-CPT. The ratings of the therapeutic alliance by patients and therapists were strongly correlated (r = .512, p < .01); however, at session level, there was a significant difference between the patients’ and their therapists’ alliance assessments. Patients with a higher perceived therapeutic alliance showed a greater reduction in self-reported symptoms over the course of therapy, compared to patients with lower alliance ratings. However, this only applied to the therapeutic alliance assessed by the patients. Discussion The therapeutic alliance plays a crucial role in D-CPT with young patients, contributing to a reduction in symptom severity over the course of treatment. It is essential that therapists prioritize the development of a strong alliance and seek feedback from their patients. The results suggest that patients’ perceptions, which often differ from therapists’ assessments, were more important in determining treatment success in the sample. Studies with larger samples sizes and additional independent ratings of alliance are needed to further examine the alliance-outcome link. Trial registration The trial was registered at the German Clinical Trial Registry, DRKS00004787, 18 March 2013, https://www.drks.de/DRKS00004787 .